A Defense of Form: Internet Memes and Confucian Ritual - Brown, Nicholas (Stance: an international undergraduate philosophy journal, 2019)
By applying the normative basis of Confucian ritual activity to the repeatable designs of internet memes, this essay explores the ways in which socially recognized forms can allow individuals to engage in thoughtful activity with what is represented by but cannot be reduced to form: the particulars of human experience. The goal of this insight is to suggest that the value of art and ideas cannot be isolated from how individuals interact with them, and thus critique should examine how well an idea or piece promotes an active, creative, and critical relationship to a person’s own experiences.